Application of medical physical culture at extensive superficial burns of the I-II degree - Vjacheslav Meleshkov (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to study and prove purpose of medical physical culture at extensive superficial burns of the I-II degree for normalization of exchange processes, the prevention of the developments of stagnation connected with the compelled decrease in physical activity. Materials and Methods: analysis and generalization of scientific and methodical literature. Results: the main means of physical rehabilitation - medical physical culture is considered; its application at treatment of patients with extensive superficial burns of the I-II degree is proved; techniques of medical physical culture in the period of little burn shock and in the period of a sharp toksemy are described in detail. Conclusions: it is established that occupation duration remedial gymnastics depends on a condition of the patient and objectives. In each occupation the all-strengthening, breathing and special exercises, as a rule, have to be applied. The most important feature of a technique of occupations at a burn disease is need of repeated performance during the day of the special exercises directed on prevention or elimination of malfunction of the musculoskeletal device